Appendix A, Rules and Regulations Governing the Public Parks within the City of Haverhill (1905) - (:unkn) unknown (My University, 1905)
It is forbidden . . . 9. To throw stones, balls or other missiles; to discharge or carry firearms, torpedoes, firecrackers or fireworks
Keywords: CARRY; DISCHARGE